Monitoring and Notification System Air Quality Against Carbon Monoxide in The Study Room IoT based - Duesa, Made Ayu; Sari, Kartika Rahayu Tri Prasetyo (INTENSIF: Jurnal Ilmiah Penelitian dan Penerapan Teknologi Sistem Informasi, 2021)
The increase in human activities has triggered air pollution, especially in school areas. It results from various kinds of gases from exhausts or combustion that harm health and air quality for the community. The source of air pollution from motorized vehicles is one of the most significant contributors to air pollution in the school area. To prevent and control air pollution, a tool is needed to measure the gas levels. In this study, the tool used has a feature of monitoring air quality with the Internet of Things (IoT) platform. An essential part of this device is a sensor based on a microcontroller, where The device will send the data obtained by the MQ135 sensor module to the IoT platform. People can access information about air quality via smartphone devices for air quality information in the study room. This study's average result in detecting air quality is 495, indicating a moderate level of air pollution. With the existence of an air quality monitoring and notification system in this study room, it has the potential for awareness about the importance of healthy air quality for the community, especially students who will become the nation's next-generation students 8 hours learning environment.